Economic assessment of mud crab (Scylla Serrata) culture as an adaptation strategy to salinity intrusion in south-west region of Bangladesh. Issue 6 (2nd November 2018) - Basu, Sudipa; Roy, Apurba
Abstract: This paper examines the effectiveness of crab culture as an adaptation strategy against salinity intrusion in the south-west region of Bangladesh. The research uses descriptive statistics, such as mean, standard deviation, benefit-cost analysis, Cobb-Douglas production function, and total barrier index to show the socio-demographic information of the respondents and profitability, efficiency, and returns to scale along with barriers to crab culture. Simple random sampling has been used to select the sample from the study area. The result from benefit-cost analysis shows that crab production is economically viable and profitable. The estimated results from the Cobb-Douglas production function model indicate the positive influence of crab feed and crab seed on total yield of crab production. There are increasing returns to scale in crab production system where there is still scope to increase productivity of crab production. A few barriers to crab production have been identified. High feed cost and lack of credit are the top barriers to crab culture.